Comparative efficacy of parathyroidectomy and active surveillance in patients with mild primary hyperparathyroidism: a systematic review and meta-analysis. Issue 12 (December 2016) - Singh Ospina, N.; Maraka, S.; Rodriguez-Gutierrez, R.; Espinosa de Ycaza, A.; Jasim, S.; Gionfriddo, M.; Castaneda-Guarderas, A.; Brito, J.; Al Nofal, A.; Erwin, P.; Wermers, R.; Montori, V.
Abstract Counseling for patients with primary hyperparathyroidism (PHPT) and mild hypercalcemia without indications for surgical intervention requires accurate estimates of the potential benefits of parathyroidectomy. We aim to summarize the available evidence regarding the benefits of parathyroidectomy that patients with mild PHPT without indications for surgery experience compared to observation. We searched multiple databases from inception to August 2015. We included randomized controlled trials (RCT) and observational studies that evaluated changes in bone health, quality of life or neuropsychiatric symptoms, or in the risk of nephrolithiasis, cardiovascular events, or death between patients undergoing parathyroidectomy or active surveillance. Eight studies were eligible. Risk differences were not significant, in part due to lack of events (fractures, nephrolithiasis, cardiovascular events, or deaths). No significant differences were observed across measures of bone health, quality of life, and neuropsychiatric symptoms. A single RCT evaluating bone mineral density (BMD) changes at 5 years found a small statistically significant effect favoring parathyroidectomy. Patients with mild PHPT without indications for surgery experience a limited number of adverse consequences during short-term follow-up limiting our ability to estimate the benefit of surgery during this timeframe. This information is helpful as these patients consider surgery versus active surveillance. Long-term data is warranted to determine who benefits in the long run from surgical intervention and the extent to which this benefit affects outcomes that matter to patients.